Pengaruh Tingkat Receivable Financing dan Inventory Financing Terhadap Profitabilitas di BSI KCP Medan Iskandar Muda - M. Ridwan; Ahmad Fauzi Sitorus (ITB AAS INDONESIA Surakarta, 2023)
This research is motivated by the fact that financing is the main source of income for banks. Profitability is a measuring tool used to determine how far a bank has progressed towards the goal of increasing bank profits. Equity financing, including debt financing under Qardh contracts(debt financing) and inventory financing under sales agreements (inventory financing), can affect the Bank's income. In addition, the increase in outflow of funds from banks is expected to affect the income of Islamic banks. The researcher examines the effect of receivables and inventories on the profitability of BSI KCP Medan Iskandar Muda in these cases. This research was conducted at BSI KCP Medan Iskandar Muda Medan Iskandar Muda The data analysis method used is quantitative. The data collection technique used in this thesis is in the form of documentation of the financial statements of Indonesian Islamic banks in 2017-2021